ANALISIS KECENDERUNGAN PENOKOHAN DALAM NOVEL TAHAJJUD CINTA KARYA MUHAMMAD EL NATSIR - Tato Nuryanto (Indonesian Language Education and Literature, 2016)
Aims this research to describe the tendency review characterizations character through character and physical state figures novel â€œTahajjud Cintaâ€ by Muhammad El Natsir. The methods used hearts singer research is descriptive method because singer feels suitable method to know and explain the phenomenon of characteristics of the individual, the situation specific groups operate accurate, especially leaders a new hearts. The summarized based on analysis: First, the character of Muhammad Abdul Fateh leaders more hearts find â€œTahajjud Cintaâ€ by Muhammad El Natsir. Second, as the fatih physical state key figures hearts novel singer described that his body is very athletic, and handsome. Third, the supporting cast hearts novel character â€œTahajjud Cintaâ€ by Muhammad El Natsir can be helpful and clarify top figures. Fourth, the physical state of the supporting cast few hearts novel singer participate be highlighted so that researchers can determine the state of the overall operate physical supporting cast.